The Future of Multi-Cloud Strategies: Orchestrating Innovation Across Distributed Environments - Uday Kiran Yedluri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapid evolution of multi-cloud architectures has fundamentally transformed enterprise IT operations, enabling organizations to distribute workloads strategically across multiple providers. This article explores the maturation of multi-cloud strategies through several critical dimensions: the historical progression from single to multi-cloud deployments, advanced orchestration frameworks leveraging containerization and Infrastructure-as-Code methodologies, AI-driven optimization capabilities that enhance both performance and cost-efficiency, and the complex security and compliance considerations inherent in distributed environments. The article demonstrates how organizations achieve substantial operational improvements while addressing industry-specific challenges through detailed case studies spanning financial services, healthcare, retail, and manufacturing sectors. The article identifies emerging trends in distributed cloud architectures and highlights strategic implications for future IT infrastructure management, emphasizing the critical role of standardized practices and organizational capabilities in achieving multi-cloud maturity.